2001
DOI: 10.1016/s0014-5793(01)02984-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Rac activation in thrombin‐ and collagen‐stimulated human blood platelets

Abstract: In this study, we characterised the mechanisms of Rac GTPase activation in human platelets stimulated by two physiological agonists, either thrombin, acting through membrane receptors coupled to heterotrimeric G-proteins, or collagen which is known to mobilise a tyrosine kinase-dependent pathway. Both agonists induced a rapid activation of Rac that was not significantly affected by the inhibition of integrin K K IIb L L 3 engagement. Using pharmacological inhibitors, we found that phospholipase C activation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
65
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 40 publications
(70 reference statements)
9
65
0
Order By: Relevance
“…It has been reported that collagen stimulates Rac GTPase activation in human platelets and that Rac is essential for thrombus formation (12,13). We found that collagen marke dly increased the levels of GTP-Rac in human platelets in a time-dependent manner.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…It has been reported that collagen stimulates Rac GTPase activation in human platelets and that Rac is essential for thrombus formation (12,13). We found that collagen marke dly increased the levels of GTP-Rac in human platelets in a time-dependent manner.…”
Section: Discussionsupporting
confidence: 48%
“…As regards Rac in platelets, it has been shown that platelets express the Rho family, including Rac (12). In addition, collagen and thrombin reportedly stimulate the activation of Rac, which is critical for thrombus formation (12,13). However, the exact role of Rac in human platelets has not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…In other cell systems, RhoG is known to activate Rac via interaction with ELMO and DOCK180 (21)(22)(23). Previous studies have shown that Rac1 is activated in platelets by a number of agonists (45)(46)(47) and plays an important role in aggregation, secretion, and clot retraction. Interestingly, Rac1 is known to be essential for the regulation of PLC␥2 in platelets downstream of GPVI or CLEC-2 (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to Rac in platelets, it has been demonstrated that platelets express the Rho-family GTPases, including Rac (9). Additionally, in platelets, collagen and thrombin reportedly stimulate the activation of Rac, which is important in thrombus formation (9,10). However, the exact role of Rac in human platelets remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%